Biofilm Formations in Nasopharyngeal Tissues of Patients with Nasopharyngeal Osteoradionecrosis. Issue 4 (24th January 2013) - Tsai, Yih‐Jeng; Lin, Yu‐Chi; Wu, Wen‐Bin; Chiu, Po‐Han; Lin, Brian J.; Hao, Sheng‐Po
Abstract : Objective: Determine the presence of nasopharynx biofilms in patients with nasopharyngeal cancer (NPC) and osteoradionecrosis (ORN) and patients with NPC but no ORN. Study Design: Cross‐sectional study. Setting: Tertiary referral medical center. Subjects and Methods: We enrolled 27 patients with NPC from our outpatient clinic during January 2010 to June 2012. These patients were diagnosed with NPC between 1980 and 2012, and all had received radiotherapy. Of these 27 patients, 15 presented with ORN, and 12 did not. The nasopharynx biopsied specimens were processed and analyzed within 2 hours of collection with the FilmTracer LIVE_DEAD Biofilm Viability Kit (Molecular Probes, Invitrogen, Carlsbad, California). A blinded investigator determined the formation of biofilms by fluorescence microscopy. Bacterial cultures were collected. Results: Eleven of 15 (73%) ORN patients had biofilm formations in nasopharynx biopsy specimens. Five of these samples (45%) yielded positive cultures, and 4 of these cultures indicated the presence of methicillin‐resistant Staphylococcus aureus (MRSA). Only 1 of 12 NPC patients without ORN had nasopharynx biofilm formation, and all culture results were negative. Conclusion: Biofilm formations were common in nasopharynx samples of NPC patients with ORN but rare in samples of NPC patients without ORN. The presence of biofilms, especially MRSA, may have a role in the disease progression of ORN or may contribute to the chronicity and resistance to antibiotic treatment.